The influence of organizational socialization on Finnish expatriates’ cross-cultural adjustment in Southeast Asia - Vammelvirta, Heidi (My University, 2013)
Due to the rapid rise of globalization over the past half century, business has become increasingly international. The demand for competent expatriates is increasing, because they can implement the parent company’s strategy and share the knowledge in the host company. Despite the increased need of expatriates and growing interest to work abroad, a large number of expatriates fail. Expatriation can be extremely challenging because of differences in such things as language, cultural values and expectations. Expatriates have to adjust to the new environment and they undergo an international adjustment process, which includes work, general and interaction adjustment. It can be assumed that organizational socialization is also a factor that has an effect on international adjustment. Expatriation has increased especially in Southeast Asia, which is a growing market area and has a great potential in many business fields. However, despite of great advantages there are still serious challenges and risks in doing business in Southeast Asia. The purpose of this thesis is to present factors that influence international adjustment process and analyze how organizational socialization process happens in the context of expatriates’ international adjustment. The intention is to research if organizational socialization is an influencing factor in international adjustment process and what are the possible effects on adjustment. Cultural point of view is also taken into account and the cultural dimensions of Finland and Southeast Asia are presented. The focus is on Finnish expatriates in Southeast Asia. This study is phenomenological, theory -based research, which uses IPA (interpretative phenomenological analysis) approach. Data was collected through non- standardized semi-structured interviews. There were 9 interviewees, both male- and female expatriates who were working or had been working in Southeast Asia. It was found that organizational socialization has an effect on expatriates’ international adjustment. Especially co-worker support was a positive predictor of successful adjustment. Also training and understanding about culture and one’s work was also important in the adjustment process. From the point of view of cross-cultural adjustment model, especially expatriates’ individual factors, cultural novelty and logistical support had an effect on adjustment.
Keywords: Expatriate; cross-cultural adjustment; organizational socialization process; Southeast Asia; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|